2020
DOI: 10.1002/rcs.2089
|View full text |Cite
|
Sign up to set email alerts
|

Head‐up display assisted endoscopic lumbar discectomy—A technical note

Abstract: Background: Minimally invasive surgery is heavily dependent on indirect visualization and image guidance, often resulting in non-ergonomic postures. Minimally invasive surgeons are more likely to experience neck pain, shoulder pain, and fatigue compared to open surgeons. Spinal endoscopy is rapidly increasing in popularity among minimally invasive spine surgeons. A primary ergonomic issue is the position of the endoscope display, which is often not in line with the operative field or the surgeon's natural line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Furthermore, it will enable surgeons to proceed with surgery without taking their attention away from the procedure, resulting in shorter operative times and reduced radiation exposure [67][68][69]. In the field of neurospine surgery, several attempts to use smart-glass displays as intraoperative neuromonitors [70], endoscopic monitors [71], display devices for fluoroscopy [68], and 3D navigation screens [67,69] have been reported. Moreover, with VR-HMD as a video viewing device, the 360 • operative images and surgeon view with action camera can provide residents and medical students with a sense of immersion and realism, allowing them to experience surgery in an educational way, rather than by just observing it [20,22].…”
Section: Viewing Via Hmdmentioning
confidence: 99%
“…Furthermore, it will enable surgeons to proceed with surgery without taking their attention away from the procedure, resulting in shorter operative times and reduced radiation exposure [67][68][69]. In the field of neurospine surgery, several attempts to use smart-glass displays as intraoperative neuromonitors [70], endoscopic monitors [71], display devices for fluoroscopy [68], and 3D navigation screens [67,69] have been reported. Moreover, with VR-HMD as a video viewing device, the 360 • operative images and surgeon view with action camera can provide residents and medical students with a sense of immersion and realism, allowing them to experience surgery in an educational way, rather than by just observing it [20,22].…”
Section: Viewing Via Hmdmentioning
confidence: 99%
“…Kaneko et al and Lim et al examined the merits of using smart glasses during an ultrasound-guided procedure in their randomized control studies, and these investigators concluded that smart glasses improved ergonomic efficiency by reducing head movements. 4,6 In the field of neurospine surgery, several attempts to use smart glasses displays as an intraoperative neuromonitor, 8 endoscopic monitor, 9 or 3D navigation screen have been reported. Yoon et al investigated the feasibility of streaming navigation images onto smart glasses during pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…2). 9 When using a wireless connection, surgeons can perform procedures more comfortably with full-body mobility.…”
Section: Discussionmentioning
confidence: 99%
“…AR displays are heads-up displays (HUDs) that show the same information as spinal navigation computer screens, directly onto the surgeon’s AR headset. Dr. Urakov has been able to demonstrate this when he successfully reported on an endoscopic lumbar discectomy with the direct endoscopic images being displayed to the surgeon’s lenses [ 28 ]. With direct line of sight of navigation/imaging, surgeons can also apply this technology to more complex cases.…”
Section: Discussionmentioning
confidence: 99%